Preparation and evaluation of antimicrobial activity of nanosystems for the control of oral pathogens Streptococcus mutans and Candida albicans - Pupe CG (Dove Medical Press, 2011)
Carolina Gonçalves Pupe1, Michele Villardi1, Carlos Rangel Rodrigues1, Helvécio Vinícius Antunes Rocha2, Lucianne Cople Maia3, Valeria Pereira de Sousa1, Lucio Mendes Cabral11Depto de Medicamentos, Faculdade de Farmácia, UFRJ, Rio de Janeiro, 2Farmanguinhos/FIOCRUZ, Rio de Janeiro, 3Faculdade de Odontologia, UFRJ, Rio de Janeiro, BrazilBackground: Diseases that affect the buccal cavity are a public health concern nowadays. Chlorhexidine and nystatin are the most commonly used drugs for the control of buccal affections. In the search for more effective antimicrobials, nanotechnology can be successfully used to improve the physical chemical properties of drugs whilst avoiding the undesirable side effects associated with its use. Herein described are studies using nystatin and chlorhexidine with sodium montmorillonite (MMTNa), and chlorhexidine with ß-cyclodextrin and two derivatives methyl-β-cyclodextrin and hydroxypropyl-β-cyclodextrin in the development of antimicrobial nanosystems.Methods: The nanosystems were prepared by kneading and solubilization followed by freeze-drying technique. The nanosystems were characterized by X-ray powder diffraction (XRPD), differential scanning calorimetry (DSC), and Fourier transform infrared spectroscopy (FTIR). Nanosystem antimicrobial activity against Streptococcus mutans and Candida albicans strains was evaluated with inhibition halo analysis.Results: The nanocarriers MMTNa and cyclodextrins showed good yields. XRPD, FTIR, and DSC analysis confirmed the proposed nanosystems formation and the suitability of the production methods. The nanosystems that showed best antimicrobial effect were chlorhexidine gluconate (CHX) and cyclodextrin inclusion complexes and CHX:MMTNa 60% cation exchange capacity – 24 hours.Conclusion: The nanosystem formulations present higher stability for all chlorhexidine inclusion complexes compared with pure chlorhexidine. The nystatin nanosystems have the potential to mask the bitter taste, justifying subsequent in-vivo studies. For these reasons, further studies are being carried out to evaluate their application in professional formulations.Keywords: sodium montmorillonite, chlorhexidine gluconate, buccal diseases, nanotechnology, cyclodextrins